An Overview of the Proposed Guidelines to Standardise the Respirable Dust Sampling Strategy for Risk Determination in Collieries (The Australasian Institute of Mining and Metallurgy, 1988)
The introduction of gravimetric sampling of respirable dust in the mining industry ne- cessitated the standardisation of techniques. The paper reviews the legislation con- trolling respirable dust monitoring for risk assessment purposes, it discusses the actions taken to introduce gravimetric sampling in collieries and it summarises the proposed guidelines. In conclusion, some of the results of dust surveys conducted in accordance with the proposed strategy are discussed.